2022
DOI: 10.1007/s00216-022-04237-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of COVID-19-related biomarkers by electrochemical biosensors and potential for diagnosis, prognosis, and prediction of the course of the disease in the context of personalized medicine

Abstract: As a more efficient and effective way to address disease diagnosis and intervention, cutting-edge technologies, devices, therapeutic approaches, and practices have emerged within the personalized medicine concept depending on the particular patient's biology and the molecular basis of the disease. Personalized medicine is expected to play a pivotal role in assessing disease risk or predicting response to treatment, understanding a person's health status, and, therefore, health care decision-making. This work d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 283 publications
0
21
0
Order By: Relevance
“… 298 To achieve this goal, it is critical to develop biosensors to detect biomarkers such as viral molecules, ACE2 receptor, vitamin D levels, IgG, IgM antibodies, and C-reactive protein to help medical professionals to diagnose infection, determine the risk of infection, monitor immune response, and assess disease severity. 299 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 298 To achieve this goal, it is critical to develop biosensors to detect biomarkers such as viral molecules, ACE2 receptor, vitamin D levels, IgG, IgM antibodies, and C-reactive protein to help medical professionals to diagnose infection, determine the risk of infection, monitor immune response, and assess disease severity. 299 …”
Section: Discussionmentioning
confidence: 99%
“…298 To achieve this goal, it is critical to develop biosensors to detect biomarkers such as viral molecules, ACE2 receptor, vitamin D levels, IgG, IgM antibodies, and C-reactive protein to help medical professionals to diagnose infection, determine the risk of infection, monitor immune and assess disease severity. 299 Technological advances opened a new door to many aspects of ribosome biogenesis. Several new technologies, such as polysome profiling, ribosome-sequence, cryo-electron microscopy, and translating ribosome affinity purification, can accurately assess ribosome morphology, structure, translocation, ribosome-"frameshift", ribosome-stalling, and ribosome-collision.…”
Section: Discussionmentioning
confidence: 99%
“…can helpful in determining the viral infection in patients. [27] It is also found that vitamin D deficiency can be a determining factor in suseptability towards COVID-19 infection. [29] In addition, serum albumin, glucose and protein levels in urine etc have been found to be high in critically affected people.…”
Section: Pathophysiology Of Sars-cov-2mentioning
confidence: 99%
“…Others: micro RNAs, total testosterone, creatine kinase, bradykinin, pulmonary microbiota etc. can helpful in determining the viral infection in patients [27] . It is also found that vitamin D deficiency can be a determining factor in suseptability towards COVID‐19 infection [29] .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation